Comparison of Oral versus Intravenous Fluid Therapy on Amniotic Fluid Index in Women with Oligohydramnios: Oral Versus Intravenous Fluid Therapy on AFI in Women with Oligohydramnios - Shahid, Maryam; Tariq, Sofia; Farzana, Mahwish (Pakistan Journal of Health Sciences, 2025)
Oligohydramnios, characterized by reduced amniotic fluid volume, poses significant risks to fetal growth and pregnancy outcomes. Objectives: To compare the effects of oral versus intravenous fluid therapy on AFI in women with oligohydramnios, and to determine the more effective hydration strategy for clinical use. Methods: Following ethical approval from the Institutional Review Board of Fatima Jinnah Medical University, a quasi-experimental study was conducted. 60 patients diagnosed with oligohydramnios based on operational criteria were enrolled after obtaining written informed consent. Participants were randomly divided into two groups: Group A received IV hydration, while Group B received oral hydration. Both groups remained admitted for one week, during which AFI was measured at baseline and after the intervention. Results: The mean age of participants was 27.67 ± 6.00 years. Baseline AFI was 3.79 ± 0.25 cm, with no significant differences between groups. After one week, Group A (IV hydration) showed a mean AFI of 5.34 ± 0.23 cm, while Group B (oral hydration) achieved a significantly higher mean AFI of 5.69 ± 0.41 cm (p=0.000). Treatment efficacy was reported in 90.0% of Group A and 96.7% of Group B participants (p=0.612). Conclusions: The improvement in AFI with oral hydration was slightly better than with IV hydration, but not statistically significant. The two interventions were safe with no maternal or fetal adverse effects. The first option is oral hydration, which is practical, non-invasive, and cost-effective, especially in resource-restricted settings.